Traumatic Effects on Post Covid English Language Teaching and Learning - Kshetree, Arun Kumar (Butwal Campus Journal, 2022)
This article is based on the paper presented as the key note speech in the National Conference organized by Siddhartha Campus Kapilvastu. The main objective of this paper is to analyze the post COVID challenges and opportunities in education sector specially focusing on the ELT classes. There were drastic changes in ELT situation during the COVID-19 period which created long term impact in the students and teachers as well as the school administration even after the pandemic situation. The lockdown period terror and the shifting the modalities of teaching and learning of English were really torturing to not only the students and teachers but also to the parents of the students and the family members of the teachers. The traumatic effect of that time affected the teaching learning for some time after the situation came to normal and it also taught some long-term skills in all.